(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
The Public Administration demands to adjust to the current world, and in this sense the present article is disclosed. In it, a theoretical review of several authors who have dedicated themselves to study, topics related to Public Administration, Public Management, Human Development, Governance and Globalization, is offered. It is interesting to review the approaches of these topics after the Second World War. and how the changes of our times influence and shape the philosophical and organic aspects of the State in the XXI century, which, according to historical periods, corresponds to the postmodern era, so as to characterize the emerging paradigm and its episteme.